EXAMINATION OF THE FACTORS THAT INFLUENCES ADVERTISING LIKEABILITY OF ALCOHOLIC BEVERAGES AMONG SELECTED CONSUMERS IN KUMASI, GHANA - Tando, Isaac; Amankwah, Samuel Yaw (International Journal of Psychosocial Rehabilitation, 2020)
The study sought to examine advertising likeability and its effects on the choice of alcoholic beverage by Ghanaian consumers. Specifically, the study sought to identify factors that make alcoholic beverage adverts likeable and was also to examine the effects of advertising likeability on consumer choice of alcoholic beverage amongst selected consumers. The study adopted a descriptive survey design method. The study population included customers of beer bars and pubs located within the Kumasi Metropolis in the Ashanti region of Ghana. A sample of 300 was selected to partake in the study using a convenient sampling technique. The study utilized questionnaires to collect data for the study. Data were mainly analyzed using SPSS where one-sample t-test, frequency and regression analysis were all used. Findings showed that humour), originality/ingenuity, clear meanings, adverts with energy, adverts that rub people the wrong way,adverts with warmth, providing historical backgrounds/facts, being informative, being educational and stimulating thinking or discussion were all factors that make alcoholic beverage advertisements likeable. The study also showed that advertising likeability makes alcohol advertisements more credible, makes products easier to choose, gives perceptions of quality, makes products more appealing and significantly influences consumer’s choice of product. In confirming this finding, linear simple regression showed that advertising likeability has a significant effect on consumer choice. Based on the findings, the study recommended that alcoholic beverage producing companies tailor advertisements to get customer attention, ensure adequate levels of humour in advertising and continuously improve the effectiveness of advertising.